Smartphone dependency and mental health among Chinese rural adolescents: the mediating role of cognitive failure and parent–child relationship - Chen, Lilan (Frontiers in Psychology, 2023)
Background: With the widespread use of smartphones in daily life, smartphone dependency has become a global problem, especially among adolescents. Existing researches have supported the association between smartphone dependency and mental health of Chinese rural adolescents, but the underlying mechanism is still unclear.The present study used a survey to test whether smartphone dependency may be associated with mental health of Chinese rural adolescents. The mediating role of cognitive failure and parent-child relationship were also examined.941 adolescents (45.91% male; mean age = 14.05, SD = 1.04) in rural areas of mainland China were recruited to complete four scales, including Mobile Phone Dependence Scale (MPDS), Cognitive Failures Questionnaire (CFQ), Family Adaption and